Radiofrequency Microdebridement as an Adjunct to Arthroscopic Surgical Treatment for Recalcitrant Gluteal Tendinopathy: A Double-Blind, Randomized Controlled Trial. Issue 1 (24th January 2020) - Blakey, Caroline M.; O'Donnell, John; Klaber, Ianiv; Singh, Parminder; Arora, Manit; Takla, Amir; Fitzpatrick, Jane
Background: Recalcitrant greater trochanteric pain is increasingly recognized as an indication for surgical intervention. The arthroscopic approach has become rapidly more common than the open alternative. Hypothesis: Patients undergoing radiofrequency microdebridement (RFMD) as an adjunct to arthroscopic gluteal bursectomy (AGB) and iliotibial band release (ITBR) will experience better functional improvement than AGB and ITBR alone at 1 year. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 33 patients with failed nonoperative treatment of gluteal tendinopathy were randomly allocated to undergo AGB/ITBR or AGB/ITBR + RFMD. Full-thickness tears were excluded. The primary outcome measure was the modified Harris Hip Score (mHHS) at 52 weeks. Secondary outcome measures included the mHHS, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), visual analog scale (VAS) for pain, and 12-item Short Form Health Survey (SF-12), which were evaluated at 0, 6, 12, 24, and 52 weeks. Statistical significance was defined as P < .05. Results: A total of 33 participants (33 hips; 30 female and 3 male; mean age, 58 years) were randomized; 16 patients underwent AGB/ITBR + RFMD, and 17 underwent AGB/ITBR. Participants' functionality improved in both groups at all time intervals. The mean mHHS score improved from 57.49 ± 10.61 to 77.76 ± 18.40 ( P = .004) and from 58.98 ± 12.33 to 79.96 ± 18.86 ( P = .001) at 52 weeks in the AGB/ITBR and AGB/ITBR + RFMD groups, respectively, although there was no statistically significant difference between groups. There were no device-related adverse events. Conclusion: AGB/ITBR led to significant improvements in patients with recalcitrant gluteal tendinopathy. In this small RCT, the addition of RFMD showed no additional benefit to AGB/ITBR but provided a safe adjunct for the surgical management of recalcitrant gluteal tendinopathy. Registration: NCT01562366 (ClinicalTrials.gov identifier).